Exploring the relationship between social support and college commitment of first-generation college students - Garcia, Ariana, author; Gonzalez, Jessica, advisor; Carlson, Laurie, committee member; Scott, Malcolm, committee member (Colorado State University. Libraries, 2018)
This study sought to determine the relationship between social support and the commitment to college of first-generation college students (FGCS). Previous research shows that social supports can present differently between FGCS and non-FGCS (Dennis, Phinney, & Chuateco, 2005). This study used the adapted version of the Student Adaptation to College Questionnaire (Baker & Siryk,1989) and the Social Provisions Scale (Cutrona & Russell, 1987). The researchers explored the relationship between social support and commitment to staying in college of FGCS. Participants (N = 61) were students at a large western university. Results indicated that there was a relationship between social support and commitment to college.
Keywords: counseling; higher education; commitment to college; social support; first-generation college student